[tex]a)\\\\\frac{1}{3}x-2=x+2\\\\\frac{1}{3}x-x=2+2\\\\-\frac{2}{3}x=4\ \ |*(-\frac{3}{2})\\\\x=-6[/tex]
[tex]b)\\\\1-\frac{6}{7}x =\frac{4}{7}\\\\-\frac{6}{7}x =\frac{4}{7}-1\\\\-\frac{6}{7}x =-\frac{3}{7}\ \ |*(-\frac{7}{6})\\\\x=\frac{1}{2}[/tex]
[tex]c)\\\\ 6(\frac{1}{4}x-2)=18\\\\\frac{3}{2}x-12=18\\\\\frac{3}{2}x=18-12\\\\\frac{3}{2}x=6\ \ |*(\frac{2}{3})\\\\x=4[/tex]
[tex]d)\\\\ \frac{x}{6} -\frac{1}{6}=1\\\\\frac{x}{6} =1 +\frac{1}{6}\\\\\frac{x}{6} =1 \frac{1}{6} \\\\\frac{x}{6} = \frac{7}{6}\ \ |*6\\\\x=7[/tex]
[tex]e)\\\\ -2(2x-1)=\frac{x}{3}\\\\-4x+2=\frac{x}{3}\ \ |*3\\\\-12x+6=x\\\\-12x-x=-6\\\\-13x=-6\ \ |:(-13)\\\\x=\frac{6}{13}[/tex]
[tex]f)\\\\ \frac{2}{5}(3-x) =-2\ \ |*5\\\\2(3-x)=-10\\\\6-2x=-10\\\\-2x=-10-6\\\\-2x=-16\ \ |:(-2)\\\\x=8[/tex]
[tex]g)\\\\ \frac{3}{4}(2-3x)=-6\ \ |*4\\\\3(2-3x)=-24\\\\6-9x=-24\\\\-9x=-24-6\\\\-9x=-30\ \ |:(-9)\\\\x=\frac{30}{9}=\frac{10}{3}[/tex]
[tex]h)\\\\ \frac{1}{5}(x-3)= 9-x\ \ |*5\\\\x-3=45-5x\\\\x+5x=45+3\\\\6x=48\ \ |:6\\\\x=8[/tex]
[tex]i)\\\\\frac{0,6+x}{2}=x+1\ \ |*2\\\\0,6+x=2x+2\\\\x-2x=2-0,6\\\\-x=1,4\ \ |*(-1)\\\\x=-1,4[/tex]